profile
Опубликовано 1 год назад по предмету Алгебра от li156

tg 3пи/4*cos 3пи/4+ctg(-пи/6)*sin пи/6

  1. Ответ
    Ответ дан Гоша68
    =tg(П/2+П/4)*cos(П/2+П/4)-cos(П/6)*sin(П/6)/sin(П/6)=-ctg(П/4)(-sin(П/4)-                         -cos(П/6)=cosП/4-cosП/6=(√2-√3)/2
  2. Ответ
    Ответ дан mukus13
    tg frac{3 pi }{4}*cos frac{3 pi }{4}+ctg(- frac{ pi }{6} )*sin frac{ pi }{6} =tg( pi - frac{ pi }{4})*cos( pi - frac{ pi }{4})-ctgfrac{ pi }{6}*sin frac{ pi }{6}==-tg frac{ pi }{4}*(-cos frac{ pi }{4})-ctgfrac{ pi }{6}*sin frac{ pi }{6} =-1*(- frac{ sqrt{2} }{2} )- sqrt{3} * frac{1}{2}= frac{ sqrt{2} }{2} - frac{ sqrt{3} }{2}= =frac{ sqrt{2}- sqrt{3}  }{2}